Level of knowledge of dental medical emergencies in dental students - Cuaquera Castillo, Joseph Florencio (2022)
Objective: To identify the level of knowledge of medical-dental emergencies in students from 4th to 6th year of the UNJBG School of Dental Medicine - Tacna, 2020. Methodology: It is a descriptive study, non-experimental design and cross-sectional. The study was carried out in a population of 77 students from fourth to sixth year. The instrument used was a questionnaire: "Level of knowledge of dental medical emergencies" with 20 closed questions; which was validated by expert judgment. Results: It was found that the level of knowledge of medical-dental emergencies, in students from fourth to sixth year, was regular with 51.95 %, according to the diagnostic dimension it was bad with 36.36 %, according to the first aid dimension it was regular with 53.25 %, and according to the pharmacological treatment dimension, it was regular with 42.86 %. Conclusion: The level of knowledge of medical-dental emergencies in students was regular; with which we can determine the little interest of the students regarding this topic. This research seeks to create interest in updated research on this topic.